Seasonal and tidal controls of the quantity and quality of dissolved organic matter at the marsh creek-estuarine interface. (5th November 2022) - Knobloch, Amanda L.J.; Neale, Patrick J.; Tzortziou, Maria; Canuel, Elizabeth A.
Abstract: Tidal marshes are an important source of dissolved organic matter (DOM) to estuaries, and DOM plays an integral role in regulating water quality and health of coastal ecosystems. However, our understanding of temporal patterns of DOM quantity and composition at the marsh-estuarine interface is limited. This study investigated temporal changes in colored DOM (CDOM), an important component of dissolved organic carbon (DOC), exchanged across a brackish marsh-estuarine system. The sources of DOC were examined using stable carbon isotope values whereas the sources of CDOM were based on spectroscopic properties, including absorbance and fluorescence excitation-emission matrices (EEMs). Samplings at the Taskinas marsh creek-interface in Virginia (USA) captured a range of tidal stages, seasons, and environmental conditions over a three-year timeseries. Water from low and high tides was used to represent marsh and estuarine endmembers, respectively. Absorbance of CDOM at 440 nm ranged from 0.83 to 6.75 m -1, and the highest values were found during low tides (mean 2.78 ± 0.21 m −1 ). EEMs were composed of three humic-like components (C1, C2, C3) and one protein-like component (C4). Generally, the terrestrial humic-like (C1) and marine humic-like (C2) components were more abundant than other measured components. Seasonally, CDOM absorbance was highest in spring and summer. Contributions of CDOM from terrestrial sources increased in spring during periods of high runoff and peaked in summer during periods of high marsh productivity. Higher contributions of terrestrially derived CDOM were also measured in fall during periods of plant senescence. The aquatic component (C4) was higher during periods of increased phytoplankton production and during periods of high microbial respiration of terrestrial and planktonic organic matter. Although the amount of marsh exported CDOM varied with season, its composition varied considerably less, especially with respect to autochthonous CDOM. In a focused study in 2018, inferences about the terrestrial versus estuarine sources of CDOM were compared to source inferences made using measurements of stable carbon isotopes (δ 13 C) of DOC and DIC. δ 13 CDOC values ranged from −32.25 to −25.91‰, indicative of wetland organic matter and humic-like DOM; δ 13 CDIC ranged from −9.69 to −3.12‰, consistent with groundwater and estuarine sources. Overall, CDOM and stable isotope measurements indicate that humic materials were the primary source of DOM at this marsh-estuarine interface, including inputs from marsh plants and soils and products from microbial degradation of marsh and terrestrial materials, with lesser contributions from aquatic sources. Highlights: CDOM absorption increased at low tide and in periods of high marsh productivity. CDOM fluorescence was dominated by terrestrial and marine humic-like components. Amount of CDOM varied seasonally but composition varied considerably less. Stable carbon isotopes can be used to augment CDOM spectroscopic analyses.